The Integrating Islamic Law and National Regulation in Protecting Children's Rights in Pesantren: A Socio-Legal Perspective - Holil Holil; Moh. Muhibbin; Nur Hasan (KURAS Institute, 2025)
Pesantren holds a strategic position in shaping the character and morals of the younger generation, but complex social dynamics present new challenges related to child protection. Various cases of physical, psychological, and sexual violence occurring in a number of Islamic boarding schools have raised public concern and highlight the suboptimal protection of children's rights in religious educational institutions. Although the government has issued the Regulation of the Director General of Islamic Education Number 1262 of 2024 concerning Child-Friendly Islamic Boarding Schools, academic studies are still limited to historical aspects and the function of Islamic boarding school education, resulting in a research gap in understanding the integration of Islamic law principles with state regulations in realizing a child-friendly Islamic boarding school education system. This research uses a qualitative approach with an empirical-legal method. Data was collected through in-depth interviews, field observations, and document studies, then analyzed descriptively-analytically by linking empirical findings with Islamic legal norms and legislation. The research findings indicate that the implementation of the child-friendly pesantren concept at Pondok Pesantren Nurul Cholil Bangkalan has been substantively successful, although it still faces structural obstacles such as limited facilities and cultural barriers like harsh traditional disciplinary patterns. In principle, pesantren practices align with the maqāṣid al-sharī‘ah in Islam and most of the indicators in Perdirjen 1262/2024. However, there is a need to improve human resource capacity and institutional commitment to ensure the effectiveness and sustainability of the program.